Examination of the Opinions of Physical Education and Sports Teachers Working in Private Schools on the Approach of Education, Teaching and Management - Abdullah Bingölbalı,; Cumaali Yavuz, (Journal of Educational Issues, 2024)
The number of private schools in our country is increasing day by day and they are in demand. As a result of this, an education sector with its own unique working conditions and standards has formed. Based on this situation, it is important for the quality of education to reveal the current situation of private schools regarding the education process from a real, impartial, and different perspective. The aim of this study is to determine the remarks of Physical Education teachers working in private schools on education, training, management processes and parent-student relations in Private Schools. The sample group of this study consists of 20 Physical Education teachers working at private schools in Turkey (in the province of Elazig) and selected according to the criterion sampling method, one of the purposive sampling methods. In the research, semi-structured and in-depth interviews were conducted with 20 teachers by using the phenomenology pattern, one of the qualitative research methods. The collected data were analyzed and themed by content and descriptive analysis methods. It has been determined that the assessment and evaluation made in these schools are not objective and do not reflect the truth. However, it has been observed that all kinds of opportunities are offered in order to increase the learning motivation of students in private education institutions, technological opportunities are high and they are used in the field of education, all kinds of sports and social activities are carried out and these have a positive effect on teaching methods and processes It has been determined in these schools that private lessons are given to some students for money and this is common. It has been observed that this situation affects the perspectives of the teachers towards the students and the students towards the teacher and the lesson and some teachers that direct students to learn formulas and memorize them instead of focusing on their thinking strategies and skills. Emphasis is placed on the selection of school administrators. In addition, it has been determined that parents are closely interested in their students and this situation affects student success closely.